Pharmacometric analysis linking immunoglobulin exposure to clinical efficacy outcomes in chronic inflammatory demyelinating polyneuropathy - Michael A. Tortorici; Theresa Yuraszeck; David Cornblath; Vera Bril; Hans‐Peter Hartung; Gen Sobue; Richard A. Lewis; Ingemar S. J. Merkies; John‐Philip Lawo; Michaela Praus; Billie L. Durn; Orell Mielke; et al. (Wiley, 2021)
Abstract The two main objectives of this analysis were to (i) characterize the relationship between immunoglobulin (Ig) exposure and chronic inflammatory demyelinating polyneuropathy (CIDP) disease severity using data from 171 patients with CIDP who received either subcutaneous Ig (IgPro20; Hizentra®) or placebo (PATH study), and to (ii) simulate and compare exposure coverage with various dosing approaches considering weekly dosing to be the reference dose. IgG pharmacokinetic (PK) parameters, including those from a previous population PK model, were used to predict individual IgG profile and exposure metrics. Treatment‐related changes in Inflammatory Neuropathy Cause and Treatment (INCAT) scores were best described by a maximum effect (Emax) model as a function of ΔIgG (total serum IgG at INCAT score assessment minus baseline IgG levels before intravenous Ig restabilization). Simulations indicate that flexible dosing from daily to biweekly (every other week) provide an exposure coverage equivalent to that of a weekly Ig dose.